Utilizing Technological Innovations and Service Design to Foster Emotional Well-Being Among Individuals with Cognitive Disorders - Shumin Fan (Art and Society, 2024)
This paper aims to explore the impact and challenges of technological innovation and service design on emotional health services for individuals with cognitive impairments. It begins by analyzing the relationship between cognitive impairments and emotional health, followed by a discussion on the application of technological innovation in emotional health services for individuals with cognitive impairments. Subsequently, it examines the influence of service design on emotional health for these individuals and the integration of technological innovation and service design. Finally, it discusses the future development direction and challenges of using technological innovation and service design to promote emotional health for individuals with cognitive impairments.